A Case of Senator Lynn Beyak and Anti-Indigenous Systemic Racism in Canada - Howell, Lisa; Ng-A-Fook, Nicholas (Canadian Journal of Education / Revue canadienne de l'éducation, 2022)
On March 7, 2017, Canadian Senator Lynn Beyak stood up in the Red Chamber and delivered a lengthy speech urging Canadians to recognise the positive aspects of the Indian Residential Schooling system that the Truth and Reconciliation Commission had failed to acknowledge. In their positions as settler teacher educators, the authors examine how Senator Beyak’s statements expose the depth of systemic settler colonialism, anti-Indigenous racisms, and unsettling beneficiary narratives here in Canada. The authors call on teacher educators to examine these systemic anti-Indigenous racisms in relation to how they can confront and disrupt settler Canadian colonialism and historical settler consciousness within teacher education and school curricula. Drawing on recent research done by educational researchers at Faculties of Education across Canada, the authors maintain that settler colonial benevolence and colonial systemic anti-Indigenous racisms can be unlearned and learned through ethical relationality, truth, and a critical praxis of reconciliation.